Optimal Siting and Sizing of Solar Power Sources in Interconnection Grid System - S Yogendra Reddy; Daka Seshi Reddy; G. Kesava Rao (Institute of Advanced Engineering and Science, 2016)
Growing concerns electrical power demand in need and necessity of daily livelihood of life. Impacted over addition power demanded there is climate impacts, environmental conditions due to conventional power generation resulted in improvement of cheaper solar power generation in the whole distribution system network, and programs offered by governments have contributed to an increment in the number of distributed energy resources (DERs) system in commercial and domestic electrical power output. It is well known that fact the non-optimal size and non-optimal siting system may lead to high power losses, bad voltage profiles and high losses of profit margins of DISCOM’s end. Therefore, this paper to determine the location best siting and filler of multiple DERs generators supported power loss, generation units, and cheaper power transfer demonstrated through IEEE 30 bus standard test system with help of Power World Simulator Package and single line drawing of 2MW solar PV power plant added to APDISCOM.